2018
DOI: 10.2147/ijn.s162466
|View full text |Cite
|
Sign up to set email alerts
|

Enhance the biocompatibility and osseointegration of polyethylene terephthalate ligament by plasma spraying with hydroxyapatite in vitro and in vivo

Abstract: PurposeThis study was designed to evaluate the biocompatibility and osseointegration of polyethylene terephthalate ligament after coating with hydroxyapatite (PET/HA) by using the plasma spraying technique in vitro and in vivo.MethodsIn this study, PET/HA sheets were prepared by using the plasma spraying technique. The characterization, the viability of bone marrow stromal cells (BMSCs), and the mRNA expression of bone formation-related genes were evaluated in vitro. The osseointegration in vivo was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Much of the literature has attributed these poor outcomes to the hydrophobic and smooth surface 26. Indeed, several studies have demonstrated that compared to their smooth counterparts, plasma-sprayed HA-coated PET or other polymer materials gain improved hydrophilicity and osteointegration 10,11,27. Both HA and CS are known as hydrophilic materials, suggesting that the composite coating of HA and CS could synergistically alleviate the hydrophobic properties of PET ligaments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the literature has attributed these poor outcomes to the hydrophobic and smooth surface 26. Indeed, several studies have demonstrated that compared to their smooth counterparts, plasma-sprayed HA-coated PET or other polymer materials gain improved hydrophilicity and osteointegration 10,11,27. Both HA and CS are known as hydrophilic materials, suggesting that the composite coating of HA and CS could synergistically alleviate the hydrophobic properties of PET ligaments.…”
Section: Resultsmentioning
confidence: 99%
“…PET sheets were purchased from Ligatech (Shanghai, China). PET sheets were coated with hydroxyapatite (HA) by using the plasma spraying technique according to the previous protocol 11. 1% (w/v) CS solution (75–85% deacetylated, mole weight 310,000–375,000 d; Sigma-Aldrich, St. Louis, Missouri, USA) in 2% (v/v) aqueous solution of glacial acetic acid was prepared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, calcium-phosphate (CaP) is characterized by excellent osteoinductivity and biocompatibility and has been applied to enhance bone ingrowth across the interface between graft and host bone. However, according to the histological findings of the previous studies [ 17 , 19 , 20 ], there was still fibrous scar tissue band instead of fibrocartilage structure at the graft−bone interface, which was far from the result of an ideal reconstruction. Some technical factors, such as the amount and homogeneity of the CaP coating, remained unknown, which may be associated with the imperfect results.…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, surface modification has been applied to PET in order to improve its biological performance and to further enhance the integration between PET and host bone [ 15 ]. Previous studies have used various bioactive substances such as graphene, CaP and bioactive glass for surface modification on PET [ [16] , [17] , [18] ]. Among them, calcium-phosphate (CaP) is characterized by excellent osteoinductivity and biocompatibility and has been applied to enhance bone ingrowth across the interface between graft and host bone.…”
Section: Introductionmentioning
confidence: 99%